Impact of pediatric exclusivity on drug labeling and demonstrations of efficacy - Wharton, Gerold T; Murphy, M Dianne; Avant, Debbie; Goldsmith, John V; Chai, Grace; Rodriguez, William J; Eisenstein, Eric L (Pediatrics (Evanston), 2014)
Besides vaccines and otitis media medicines, most products prescribed for children have not been studied in the pediatric population. To remedy this, Congress enacted legislation in 1997, known as pediatric exclusivity (PE), which provides 6 months of additional market protection to drug sponsors in exchange for studying their products in children. We reviewed requests for pediatric studies and subsequent labeling for drugs granted PE from 1998 through 2012. Regression analysis estimates the probability of demonstrating efficacy in PE trials. Variables include therapeutic group, year of exclusivity, product sales, initiation process, and small disease population. From 1998 through 2012, the US Food and Drug Administration issued 401 pediatric study requests. For 189 drugs, studies were completed and granted exclusivity. A total of 173 drugs (92%) received new pediatric labeling, with 108 (57%) receiving a new or expanded pediatric indication. Three drugs had non-efficacy trials. Efficacy was not established for 78 drugs. Oncology, cardiovascular, and endocrine drugs were less likely to demonstrate efficacy (P < .01) compared with gastrointestinal and pain/anesthesia drugs. Drugs studied later in the program were less likely to demonstrate efficacy (P < .05). Sales, initiation process, and small disease population were not significant predictors. Most drugs (173; 92%) granted exclusivity added pediatric information to their labeling as a result of PE, with 108 (57%) receiving a new or expanded pediatric indication. Therapeutic area and year of exclusivity influenced the likelihood of obtaining a pediatric indication. Positive and negative outcomes continue to inform the construct of future pediatric trials.